Studies in Ebla Onomastics, 1 - Buccellati, Giorgio
Selbstdruck für den Kongress 'La civiltà di Ebla' Rome, May 1980; sample pages from Repertory of Ebla Onomastics, 1 by G. Buccellati - M. L. Jaffe - J. R. Paul; Names ending in -NI/IÀ.